Intraarticular osteoid osteoma: MRI characteristics and clinical presentation before and after radiofrequency ablation compared to extraarticular osteoid osteoma = Das intraartikuläre Osteoidosteom : MRT-Charakteristik und klinisches Erscheinungsbild vor und nach Radiofrequenzablation im Vergleich zum extraartikulären Osteoidosteom - Germann, Thomas; Weber, Marc-André; Lehner, Burkhard; Kintzelé, Laurent; Burkholder, Iris; Kauczor, Hans-Ulrich; Rehnitz, Christoph (RöFo, 2020)
Purpose To determine MRI characteristics and the clinical presentation of intraarticular osteoid osteomas (OO) before and after treatment with CT-guided radiofrequency ablation (RFA) compared with extraarticular osteoid osteomas. Materials and Methods In a retrospective study, n = 21 patients with an intraarticular OO were matched with a control group of n = 21 patients with an extraarticular OO at a comparable anatomical position. All patients underwent CT-guided RFA and preinterventional MRI. In n = 31 cases, follow-up MR imaging was available. MR images were analyzed for morphologic features: effusion and synovitis, bone marrow edema (BME), soft tissue edema, periosteal reaction as well as T1 / T2 signal and contrast enhancement of the nidus. Recorded clinical parameters included the initial diagnosis, the course of pain symptoms after RFA and the incidence of complications. Results The nidus was detectable in all patients on MRI. BME had the highest sensitivity in both intra- and extraarticular OO (100 %). Effusion and synovitis were only observed in the intraarticular OO group (n = 21) with a perfect sensitivity and specificity (100 %) and a high negative predictive value (85 %). Soft tissue edema was significantly more present in patients with intraarticular OO (p = 0.0143). No significant differences were present regarding periosteal reaction, T1/T2 signal and contrast enhancement of the nidus (p > 0.05). BME, contrast enhancement, soft tissue edema, periosteal reaction, effusion and synovitis, if preexisting, always decreased after RFA. In 66.7 % of patients with intraarticular OO, a false initial diagnosis was made (extraarticular: 19 %). All patients were free of pain after intervention. Complications following the RFA procedure did not occur. Conclusion MRI demonstrates the nidus and thus the OO in all cases regardless of the location. The characteristic MRI morphology of an intraarticular OO includes synovitis and joint effusion, which are always present and differentiate with perfect sensitivity/specificity from an extraarticular OO. In both intra- and extraarticular OOs pathologic MRI changes at least decreased or completely normalized and the clinical results after RFA were excellent. Key Points: Citation Format
Gesehen am 18.01.2021